Impact of HPV-associated p16-expression and other clinical factors on therapeutic decision-making in patients with oropharyngeal cancer: A GETTEC multicentric study. Issue 12 (December 2018) - Culié, Dorian; Garrel, Renaud; Viotti, Julien; Schiappa, Renaud; Chamorey, Emmanuel; Fakhry, Nicolas; Lallemant, Benjamin; Vergez, Sébastien; Dupret-Bories, Agnès; Dassonville, Olivier; Poissonnet, Gilles; Santini, José; et al.
Abstract: Objectives: To analyze the impact of tumor p16 status and other clinical factors on the therapeutic decision-making process in patients with oropharyngeal squamous cell carcinoma (OPSCC). Methods: We conducted a multicenter retrospective study (GETTEC collaborative study group) enrolling all OPSCC patients with a determined p16-status considered eligible for surgery between 2009 and 2014. The impact of p16-status and other clinical factors on the therapeutic decision was evaluated in multivariate analysis. Results: A total of 476 patients were enrolled in the study, including 244 cases (51%) of p16-positive OPSCC. Overall, 223 (47%) patients underwent primary surgery, and 184 (83%) of them received postoperative radiotherapy ± chemotherapy. More patients with p16-positive OPSCC tended to undergo non-surgical treatment than did patients with p16-negative OPSCC (p = 0.10). Multivariate analysis showed that 5 factors significantly influenced therapeutic management of the patients: T-stage ≥ 3 (towards a non-surgical strategy; p < 0.001), N-stage ≥ 2a (non-surgical strategy; p = 0.02), tumor involvement of the glosso-tonsillar sulcus (surgical strategy; p = 0.002), tumor extension to the oral cavity (surgical strategy; p < 0.009) and the center of care (p < 0.001). The rate of patients directed towards a surgical strategy varied between 9% and 74% depending on the center. Conclusion: There was a non-significant trend to recommend patients with p16-positive OPSCC for non-surgical treatment. Center of care, tumor stage and tumor anatomical subsite and extensions were the main determinants of the treatment choice.